THE MEDIATING ROLE OF RISK MANAGEMENT ON TECHNOLOGICAL UNDERSTANDING, FINANCIAL LITERACY, AND SME PERFORMANCE IN MEDAN - Afif Muis Fakhri Masysur; Keulana Erwin; Rina Br Bukit (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study examines the impact of technological understanding and financial literacy on Small and Medium Enterprise (SME) performance, with risk management practices as a mediating variable among SMEs in Medan. An explanatory sequential mixed-methods approach combining quantitative and qualitative methods was employed. The population comprised culinary SMEs registered with the Medan City Department of Cooperatives, SMEs, Industry, and Trade. Data were collected via questionnaires and in-depth interviews. Quantitative analysis used Structural Equation Modeling-Partial Least Square (SEM-PLS), while qualitative data utilized a thematic approach to strengthen quantitative results. The findings show that technological understanding and financial literacy both positively affect SME performance and risk management practices. Additionally, risk management practices positively influence SME performance and successfully mediate the effects of technological understanding and financial literacy on performance. These results indicate that SMEs' capability to comprehend technology and manage finances enhances business performance more effectively when supported by sound risk management. Ultimately, integrating technological understanding, financial literacy, and risk management serves as a strategic driver to boost SME competitiveness, resilience, and sustainability.